Ratiometric Fluorescence Imaging of Cellular Polarity: Decrease in Mitochondrial Polarity in Cancer Cells1. Issue 8 (8th January 2015) - Jiang, Na; Fan, Jiangli; Xu, Feng; Peng, Xiaojun; Mu, Huiying; Wang, Jingyun; Xiong, Xiaoqing
Abstract Mitochondrial polarity strongly influences the intracellular transportation of proteins and interactions between biomacromolecules. The first fluorescent probe capable of the ratiometric imaging of mitochondrial polarity is reported. The probe, termed BOB, has two absorption maxima (λabs=426 and 561 nm) and two emission maxima—a strong green emission (λem=467 nm) and a weak red emission (642 nm in methanol)—when excited at 405 nm. However, only the green emission is markedly sensitive to polarity changes, thus providing a ratiometric fluorescence response with a good linear relationship in both extensive and narrow ranges of solution polarity. BOB possesses high specificity to mitochondria (Rr=0.96) that is independent of the mitochondrial membrane potential. The mitochondrial polarity in cancer cells was found to be lower than that of normal cells by ratiometric fluorescence imaging with BOB. The difference in mitochondrial polarity might be used to distinguish cancer cells from normal cells.